O MODELO DE KRUGMAN EXPLICA A CRISE CAMBIAL BRASILEIRA EM JANEIRO DE 1999? - Menezes, Adriano Campos (2009)
Krugman (1979) developed a canonical model of currency crises and speculative attack. Later, it was called "models of 1st generation ". In this context, this paper analyzes the model of Krugman (1979) to Brazil, in the period of January of 1995 to December of 1998. We used the test of Granger Causality to test the temporary precedence between international reserves and domestic credit. The results reveal the case of independence causality, since it didn't happen unidirectional causality, bi-directional causality or simultaneity causality. Therefore, the proposition of Kiugman (1979) is untenable.